Performance and stability analysis of all-perovskite tandem photovoltaics in light-driven electrochemical water splitting - Junke Wang; Bruno Branco; Willemijn H. M. Remmerswaal; Shuaifeng Hu; Nick R. M. Schipper; Valerio Zardetto; Laura Bellini; Nicolas Daub; Martijn M. Wienk; Atsushi Wakamiya; Henry J. Snaith; René A. J. Janssen (Nature Communications)
Abstract All-perovskite tandem photovoltaics are a potentially cost-effective technology to power chemical fuel production, such as green hydrogen. However, their application is limited by deficits in open-circuit voltage and, more challengingly, poor operational stability of the photovoltaic cell. Here we report a laboratory-scale solar-assisted water-splitting system using an electrochemical flow cell and an all-perovskite tandem solar cell. We begin by treating the perovskite surface with a propane-1,3-diammonium iodide solution that reduces interface non-radiative recombination losses and achieves an open-circuit voltage above 90% of the detailed-balance limit for single-junction solar cells between the bandgap of 1.6–1.8 eV. Specifically, a high open-circuit voltage of 1.35 V and maximum power conversion efficiency of 19.9% are achieved at a 1.77 eV bandgap. This enables monolithic all-perovskite tandem solar cells with a 26.0% power conversion efficiency at 1 cm2 area and a pioneering photovoltaic-electrochemical system with a maximum solar-to-hydrogen efficiency of 17.8%. The system retains over 60% of its peak performance after operating for more than 180 h. We find that the performance loss is mainly due to the degradation of the photovoltaic component. We observe severe charge collection losses in the narrow-bandgap sub-cell that can be attributed to the interface degradation between the narrow-bandgap perovskite and the hole-transporting layer. Our study suggests that developing chemically stable absorbers and contact layers is critical for the applications of all-perovskite tandem photovoltaics.